2009
DOI: 10.1093/icesjms/fsp016
|View full text |Cite
|
Sign up to set email alerts
|

Localization of individual mulloway (Argyrosomus japonicus) within a spawning aggregation and their behaviour throughout a diel spawning period

Abstract: Parsons, M. J., McCauley, R. D., Mackie, M. C., Siwabessy, P., and Duncan, A. J. 2009. Localization of individual mulloway (Argyrosomus japonicus) within a spawning aggregation and their behaviour throughout a diel spawning period. – ICES Journal of Marine Science, 66: 1007–1014. Mulloway (Argyrosomus japonicus) are a soniferous member of the Sciaenidae. During summer in the Swan River of Western Australia, individuals form spawning aggregations in turbid waters around high tide, during late afternoon and earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…This is most likely due to the different method of sound production which appears to be specific to the Glaucosomatid family (Mok et al, 2011). Large sciaenids, such as mulloway (Argyrosomus japonicus) or black jewfish (Protonibea diacanthus), whose reported maximum lengths are 1.81 and 1.50 m, respectively (Sasaki, 2001;Silberschneider et al, 2009), can produce calls of mean SL over 150 and up to 172 dB re 1 lPa at 1 m (Cato, 1980;McCauley, 2001;Parsons, 2010;Locascio and Mann, 2011;Parsons et al, 2012) which can propagate several hundred meters (Parsons et al, 2009(Parsons et al, , 2012. Individual G. hebraicum calls are more likely to be effective at ranges of up to around 100 m (assuming typical ambient noise levels of 80-90 dB re 1 lPa over the same bandwidth and spherical spreading as the maximum transmission loss).…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to the different method of sound production which appears to be specific to the Glaucosomatid family (Mok et al, 2011). Large sciaenids, such as mulloway (Argyrosomus japonicus) or black jewfish (Protonibea diacanthus), whose reported maximum lengths are 1.81 and 1.50 m, respectively (Sasaki, 2001;Silberschneider et al, 2009), can produce calls of mean SL over 150 and up to 172 dB re 1 lPa at 1 m (Cato, 1980;McCauley, 2001;Parsons, 2010;Locascio and Mann, 2011;Parsons et al, 2012) which can propagate several hundred meters (Parsons et al, 2009(Parsons et al, , 2012. Individual G. hebraicum calls are more likely to be effective at ranges of up to around 100 m (assuming typical ambient noise levels of 80-90 dB re 1 lPa over the same bandwidth and spherical spreading as the maximum transmission loss).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lagardère and Mariani (2006) proposed that the short grunts of French meagre (A. regius) are weaker than the long grunts. Similar results from in situ A. japonicus calls have been observed, but it was not confirmed whether pressure wave amplitude differences were due to range, weaker swim bladder twitches or multiple ray-path interference (Parsons et al, 2006;Parsons et al, 2009). Therefore measurement of many SLs may be required to categorize a fish call.…”
Section: Introductionmentioning
confidence: 86%
“…The determination of absolute numbers of mobile animals such as aggregating fish requires the ability to simultaneously census large volumes of water and to eliminate bias from multiple detections of the same fish. The sensitivity of hydrophones in areas of low ambient noise allows the discrimination of fish calls emitted at large ranges from the receiver and in some cases the ability to monitor individual fish over time, by listening and localizing their calls (Parsons et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, continental shelf fish choruses have been reported by Knudsen et al (1948), Cato (1978), McCauley and Cato (2000), Parsons et al (2009), Parsons et al (2013), andMcCauley (2012), while invertebrate chorus are also commonly reported (Everest et al, 1948;Fish, 1964;Castle and Kibblewhite, 1975;Radford et al, 2008). Some whale species are now so abundant on their summering breeding grounds that whale calls form seasonal choruses (e.g., Au et al, 2000 for Hawaiian humpbacks or Sirović et al, 2015 for blue and fin whales).…”
Section: Introductionmentioning
confidence: 97%